Development of Physics Interactive Learning Media based on Problem Based Learning assisted by SAC Application to Improve Student Problem Solving Ability - Anggriani Aristaria; Insih Wilujeng; Nadya Intan Herawati (Postgraduate, University of Mataram, 2024)
This study aims to see the feasibility and effectiveness of interactive learning media based on problem-based learning to improve problem solving skills. This type of research is research and development with ADDIE model and one group pretest-posttest design. The results showed that the physics interactive learning media was very feasible to use based on the results of the assessment from the validator with a value of 0.92. The increase in problem solving ability can be seen from the highest average pretest score of 46, in the posttest it rose to 82. It can also be seen from the results of the paired sample T-test test that the significance value <0.05 is inaccordance with the test criteria if Sig. (2-tailed) is smaller than 0.05, it means that there is a significant difference berween the result of the pretest and posttest score. The result of the paired sample T-test test are reinforced by the N-Gain test, which is 0.66, these result can be explained that N-Gain category is in the moderate category with 0.3 ≤ 0.66 ≤ 0.7. It can be said that interactive learning media is effective in improving student problem solving skills and the average improvement result are in the moderate category.